Langerhans cell histiocytosis in children with refractory diarrhoea and hypoalbuminaemia as the initial presentation: two case reports and a literature review - Yi Cao; Qing-Qing Wu; Wei-Hui Yan; Li-Na Lu; Yi-Jing Tao; Hai-Xia Feng; Yi-Jing Chu; Wei Cai; Ying Wang (BMC, 2024)
Abstract Langerhans cell histiocytosis (LCH) involving the gastrointestinal tract is a rare condition for which clinical experience is limited. We describe the cases of two patients who initially presented with chronic diarrhoea, hypoproteinaemia, and intermittent fever. These findings suggest that in cases of refractory diarrhoea accompanied by recurrent hypoalbuminaemia, especially with abdominal rash, LCH should be considered. Gastrointestinal endoscopy, biopsy, and imaging studies are essential for obtaining a definitive diagnosis. This approach might be helpful for the early recognition of gastrointestinal tract involvement in LCH.